2006
DOI: 10.1007/s11547-006-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

CT features of solitary fibrous tumour of the pleura: experience in 26 patients

Abstract: Depending on location, size and histological features, SFTP may produce a large spectrum of findings. Typical CT features of small SFTP were well-defined margins and smooth contours, homogeneous attenuation and right or obtuse angles with the pleura. Larger lesions were characterised by well-defined margins and lobulated contours, geographic pattern in enhanced CT scans, acute angles or smooth tapering margins with the pleura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…In such cases, analysis of the thymic cavity is also fundamental. In fact, in lesions of pleural origin, the thymic cavity is compressed and dislocated, contrary to what occurs in the presence of a mediastinal mass (which expands, compressing the pulmonary parenchyma without causing mediastinal shift) [43]. With the advent of modern equipment and the use of multiplanar imaging that enables detailed study of the mediastinum, it has become easier to distinguish between masses of thymic origin and lesions of the mediastinal pleura, even though it should be recalled that SFTP may also arise in the mediastinum [4].…”
Section: Diagnosi Differenziale Delle Localizzazioni Insolitementioning
confidence: 89%
See 1 more Smart Citation
“…In such cases, analysis of the thymic cavity is also fundamental. In fact, in lesions of pleural origin, the thymic cavity is compressed and dislocated, contrary to what occurs in the presence of a mediastinal mass (which expands, compressing the pulmonary parenchyma without causing mediastinal shift) [43]. With the advent of modern equipment and the use of multiplanar imaging that enables detailed study of the mediastinum, it has become easier to distinguish between masses of thymic origin and lesions of the mediastinal pleura, even though it should be recalled that SFTP may also arise in the mediastinum [4].…”
Section: Diagnosi Differenziale Delle Localizzazioni Insolitementioning
confidence: 89%
“…In questi casi, se localizzati a livello del mediastino superiore l'analisi della loggia timica risulta fondamentale. Infatti, in caso di lesioni a partenza pleurica essa apparirà compressa e dislocata controlateralmente rispetto a quanto avviene in presenza di masse mediastiniche che si espandono al suo interno mantenendo il mediastino in asse [43]. Grazie all'avvento delle apparecchiature di ultima generazione e all'utilizzo di immagini multiplanari, che permettono uno studio dettagliato del mediastino, risulta più facile distinguere fra una massa di origine timica e una lesione a partenza dalla pleura mediastinica, pur se bisogna ricordarsi che anche il tumore fibroso solitario della pleura può localizzarsi primitivamente nel mediastino [4].…”
Section: Diagnosi Differenziale Delle Localizzazioni Insoliteunclassified
“…Eroglu et al [14] reported a case of primary leiomyosarcoma of the anterior mediastinum presenting as a large (11-cm) mass without involvement of the main vessels or oesophagus, well-circumscribed, heterogeneous enhancement, associated pleural effusion but no lymphadenopathy. Cardinale et al [15] described the CT features of 26 SFTs of the pleura with benign and malignant behaviour. The authors showed that up to 50 % of the lesions were larger than 10 cm, and even the largest lesions presented well–defined margins and lobulated contours, also with heterogeneous enhancement and important areas of necrosis, and 24 % of the lesions presented identifiable intralesional vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The intratumoural enhanced vessels are usually tortuous and dilated, and probably represent tumoural pathological feeding vessels. To our knowledge, this feature has not been described as characteristic for other mediastinal or pleuropulmonary tumours than SFTs [15, 17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Such intralesional geographic pattern has been shown to correlate with myxoid changes and areas of hemorrhage, necrosis, or cystic degeneration (Figure 4f and Figure 11b and c). 3,10,12 …”
Section: Computed Tomographymentioning
confidence: 99%